Building an ex vivo model of breast cancer lung metastasis - Grey, James F.E. (2019)
Cell cultures are traditionally studied as 2D monolayers with use of 3D culture systems gradually becoming more prevalent. The advantages of 3D culture over traditional methods are numerous as they: do not force apical-basal cell polarity, allow the formation of 3D cell structure and allow the study of complex microenvironments, amongst others. The study of biological processes can be hindered by the limitations of monolayer culture. One such process is the metastasis of malignant cells, which requires understanding of different chronological biological processes for efficacious secondary tumour formation. This thesis shows how the many biological events occurring during metastasis can be broken down and subsequently scrutinised by traditional methods, to gain insight into the strategies employed by different breast cancer sub types. Understanding each individual process alone has led to significant gains in our understating of metastasis, bringing all components together is now possible when integrating cells into a bioreactor 3D culture system. Findings here have shown the metastatic strategies of ‘luminal A’ breast cancer is delamination whilst triple negative ‘basal B’ breast cancers used a nomadic, single-cell strategy. It was found that the single-cell strategy induced large changes in phenotype when cells were cultured in suspension, including an increased resistance to paclitaxel, mitochondrial health and resistance to anoikis, and a ‘suspended animation’ phenotype. Importantly, these behaviours were seen to revert to a migratory, proliferative phenotype upon re-adherence to a substrate. These findings were then tested in 3D culture systems. Embryonic lung fibroblast organoids were first tested as a 3D substrate before decellularised rat lung matrices were selected as the most representative. Rat decellularised lung matrix was tested as a substrate for mimicking metastasis in the context of bioreactor system which allowed the transfer of cells from one matrix to another via the flow of media. This thesis shows that reconstituting models of metastasis is possible outside of animal models.